2012
DOI: 10.7160/eriesj.2012.050304
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Students´ Level of Knowledge in Profile Courses of Choosen Economic Study Programmes at the FEM CULS

Abstract: To increase the educational attainment of the population is a priority that has arisen also from the pro-growth strategy of the European Union. In this regard, the quality of the teaching process in tertiary education and subsequent graduates' employability are paid substantial attention. However, the quality of knowledge and skills acquired and presented by the graduates on the labour market has not been observed so closely. The focus on quantitative aspects implies a significant risk of lowering qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Kučera, Svatošová, and Pelikán (2015) also conclude that student's performance can to some extend be predicted from results of entrance examinations. Boháčková and Brožová (2012) concluded that there are differences between the scores obtained from students of different study programs. However, that study included students from one faculty.…”
Section: Discussionmentioning
confidence: 99%
“…Kučera, Svatošová, and Pelikán (2015) also conclude that student's performance can to some extend be predicted from results of entrance examinations. Boháčková and Brožová (2012) concluded that there are differences between the scores obtained from students of different study programs. However, that study included students from one faculty.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these students also have problems with other subjects. Boháčková and Brožová (2012) who analyzed the exam grades of FEM students introduced two reasons why students could be of bad results. First they argued that some students are achieving worse results because they are not sufficiently devoted to the preparation even if they do evince the skills needed.…”
Section: Resultsmentioning
confidence: 99%